Entrepreneurial Mindset and Digital Literacy in Shaping Students’ Start-Up Decisions : The Mediating Role of Creativity - Nur Safirah; Muhammad Rakib; Hajar Dewantara (Kirana Publisher (KNPub), 2026)
This study aims to analyze the influence of entrepreneurial mindset and digital literacy on students' business start-up decisions, with creativity as an intervening variable. The research method used is quantitative research with a survey method of 163 students from the Faculty of Economics and Business, Makassar State University who own businesses using proportional random sampling techniques. Data analysis was conducted using the Partial Least Square Structural Equation Model (PLS-SEM) to test the direct and indirect relationships between variables. The results show that entrepreneurial mindset and digital literacy have a positive and significant effect on the decision to start a business. In addition, entrepreneurial mindset and digital literacy also have a positive and significant effect on student creativity. Creativity is also proven to have a positive and significant effect on the decision to start a business and acts as an intervening variable that connects how entrepreneurial mindset and digital literacy influence the decision to start a business. These findings have important implications for entrepreneurship development efforts in higher education, especially through the formation of an entrepreneurial mindset, strengthening digital literacy, and facilitating creative spaces for students to be more prepared and brave to enter the business world.